VERTICAL TRANSVERS ISOTROPY (VTI) PRE STACK DEPTH MIGRATION ANISOTROPI UNTUK PENCITRAAN STRUKTUR BAWAH PERMUKAAN YANG LEBIH AKURAT - Ibnu Rasid; Udi Harmoko; Agus Setyawan; Teguh Suroso (Youngster Physics Journal, 2012)
Anisotropic Pre Stack Depth Migration method has been carried out for 2D seismic reflection data on Line “IR” The simplest form of anisotropic media (VTI (Vertical Transverse Isotropy) was used. Theoretically, this form requires two parameters to describe the media, those are δ (delta) and ε (epsilon). δ is an anisotropy parameter that describe velocity variation near to vertical while ε is an anisotropy parameter that describe velocity variation near to horizontal. The anisotropic Pre Stack Depth Migration produce a section which has corrected build up image and has change to be the true of reflector in 67 m of depth. Base on well and seismic data calculation process, an anisotropic parameter is in the range of 0.050-0.058. Generally, Anisotropy Pre Stack Depth Migration method gave better result than isotropy Pre Stack Depth Migration. Key Word: Anisotropy, Pre Stack Depth Migration, VTI, delta, epsilon